2016
DOI: 10.15171/ehem.2017.05
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Congo red dye from aqueous solutions by a low-cost adsorbent: activated carbon prepared from Aloe vera leaves shell

Abstract: Background: Synthetic dyes have several harmful effects on human health as well as aquatic life. In this study, activated carbon (AV-AC), based on Aloe vera leaf shells, was used as a novel agricultural adsorbent, one that is low-cost and available for the removal of Congo red (CR) as a carcinogenic dye from aqueous solutions. Methods: In the batch system, the influence of different parameters like contact time, pH, adsorbent dosage, and initial CR concentration were examined on the dye removal from liquid med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…This can be attributed to availability of more binding site as the dose of raw bentonite clay increases. This is in consistence with the results obtained by Omidi-Khaniabadi et al, (2017). However, for activated carbon AVNP percentage removal of the dyes decreases with increase in adsorbent dosage from 0.1 to 3g.…”
Section: Effect Of Adsorbent Dosagesupporting
confidence: 90%
“…This can be attributed to availability of more binding site as the dose of raw bentonite clay increases. This is in consistence with the results obtained by Omidi-Khaniabadi et al, (2017). However, for activated carbon AVNP percentage removal of the dyes decreases with increase in adsorbent dosage from 0.1 to 3g.…”
Section: Effect Of Adsorbent Dosagesupporting
confidence: 90%
“…The rate of removal of the dye is higher in the beginning due to the large surface area of the adsorbent available for the adsorption of dye ions. After a certain period, only a very low increase in the dye uptake was observed because there are few active sites on the surface of the adsorbent (Khaniabadi et al 2017). From the contact time studied, it was revealed that 80 min of agitation time is enough to reach equilibrium when 100 mg/L of dyes concentration was employed.…”
Section: Effect Of Contact Timementioning
confidence: 99%
“…However, adsorption method has proven to be a promising method due to its efficiency, relatively low cost, reusability, and easy operation [9,18]. Congo red adsorption has been reported with adsorbents such as activated carbon with a removal efficiency of about 100% [19], activated carbon prepared from Aloe Vera leaves with a performance of almost 100% [20], jujuba seeds with a dye removal of 88% [21], roots of Eichhornia crassipes with 96% [22], and montmorillonite clay with 85% [23]. The use of solid waste as an adsorbent material has been extensively studied, however, such hazardous waste materials as leather have rarely been applied to this purpose.…”
Section: Adsorbentsmentioning
confidence: 99%